Impact Of Exclusive Breast Milk And Birth Weight On Incident Stunting Of Children Aged 12-24 Months - Rossi Septina; Tuti Asmawati; Lilik Susilowati; Khairil Walid Nasution (JKM (Jurnal Kebidanan Malahayati), 2023)
Pendahuluan: Stunting adalah masalah kurang gizi kronis yang disebabkan oleh asupan gizi yang kurang dalam waktu cukup lama akibat pemberian makanan yang tidak sesuai dengan kebutuhan gizi. Salah satu penyebab stunting pada balita yaitu pemberian ASI eksklusif yang tidak diberikan selama 6 bulan. Malnutrisi pada awal kehidupan mengakibatkan gagal tumbuh sehingga bayi tumbuh pendek.Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan pemberian ASI eksklusif dan ASI non eksklusif terhadap pertumbuhan dan perkembangan anak usia 12-24 bulan.Metode : Penelitian ini merupakan jenis penelitian analitik dengan desain penelitian cross sectional . Populasi penelitian ini adalah ibu yang memiliki anak usia 12-24 bulan, sampel yang digunakan adalah 30 anak dengan riwayat ASI eksklusif dan ASI non eksklusif serta anak dengan kejadian stunting. Analisa penelitian ini yaitu analisa Univariat dan Bivariat menggunakan uji chi square.Hasil Penelitian: Hasil studi univariat menunjukkan pendek 63,3%, berat badan lahir normal 62,1% dan riwayat pemberian ASI eksklusif 60%. Hasil penelitian Bivariat menunjukkan bahwa ada hubungan ASI eksklusif dengan stunting anak usia 12-24 bulan (P = 0,018), ada hubungan antara berat badan lahir dengan stunting anak usia 12-24 bulan (P = 0,011).Kesimpulan : Pada penelitian ini terlihat bahwa stunting pada anak usia 12-24 bulan masih cukup tinggi, maka perlu dilakukan bimbingan dan penyuluhan kepada orang tua untuk melakukan deteksi dini stunting dengan cara memeriksakan tinggi badannya di pelayanan kesehatan terdekat. Kata kunci : Asi Ekslusif, Berat Badan Lahir, Stunting ABSTRACT Introduction : Stunting is a chronic malnutrition problem caused by nutrient intake that is not in accordance with nutritional needs. One of the causes of stunting in children is exclusive breastfeeding is not given during six months because breast milk is needed during in baby’s growth period so that the nutritional needs are fulfilled.Exclusive breastfeeding for infants aged 0-6 months is fundamental because nutrition in breast milk can increase the growth and development of children. The impact of babies who have low birth weight (lbw) will last from generation to generation, children with LBW will have less anthropometric measurements in their development. Malnutrition in early life results in failure to thrive so the baby grows short, as well as impact on cognitive development, infant morbidity and mortality.Objective : The purpose of this study was to examine the relationship between exclusive breastfeeding and non-exclusive breastfeeding on the growth and development of children aged 12-24 months.Methods : This research is an analytic research type with a cross sectional research design . The population of this study is mothers who have children aged 12-24 months, the samples used are 30 children with a history of exclusive breastfeeding and non-exclusive breastfeeding and the children on incident stunting. The analysis of this research is Univariate and Bivariate analysis using the chi square test.Results : The results of the Univariate study showed short of stunting of 63.3%, normal birth weight of 62.1% and history of exclusive breastfeeding of 60%. The results of the Bivariate study showed that there was relationship between exclusive breastfeeding and stunting of children aged 12-24 months (P = 0.018), there was a relationship between birth weight and the stunting of children aged 12-24 months (P = 0.011).Conclusion : In this study it can be seen that stunting of children aged 12-24 months is still quite high, it is necessary to provide guidance and counseling to parents to carry out early detection of stunting by checking their height at the nearest health service. Keywords: Exclusive Breastfeeding, Birth Weight, Stunting